Pengaruh Variabel Makroekonomi terhadap Yield Spread Obligasi Pemerintah Republik Indonesia - Aurelia S.I. Ongko; Jesslyn Santoso; Kayla Lukman; Virliza I. Rahardjo; Agus Salim (Universitas Negeri Padang, 2021)
This study examines several macroeconomic factors from April 2016 to March 2021, including the BI Rate, Credit Default Swap, Inflation, and Money Supply (M2). This study uses the Autoregressive Distributed Lag (ARDL) regression method followed by Error Correction Model (ECM) analysis to see the relationship in the short term and Level Equation to determine the long term relationship between independent and dependent variables.. The results of this study finally prove that BI Rate, Credit Default Swap, and Inflation affect the long-term distribution yield spread, while the money supply (M2) does not affect it. Meanwhile, macroeconomic factors that affect the yield spread in the short-term are only the BI Rate variable.